Social Networks' Role in Online Education - Varol, Asaf; Ahmed, Naveed (Ieee, 2013)
Since students of online education do not meet face to face in a classroom environment, students get engaged to the classes via third party content or learning management tools. It is evident that young people spend most of their time on Social Networking websites when they are connected to internet. These sites provide free of speech environment without any restrictions. Moreover, the research in this area points out that the students are being more social when they use one of these Social Networking websites. Based on this findings, one can say using Social Networking in online education may provide an active cyber classroom environment with positive learning outcomes. Therefore, this paper is focusing on the role of Social Networking websites affect on student betrothal in online education.
7th International Conference on Application of Information and Communication Technologies (AICT) -- OCT 23-25, 2013 -- Baku, AZERBAIJAN
Keywords: Social Networking; Distance Learning; Online Education